The Effect of Pre-Harvest Application of Pectic Oligosaccharides and Abscisic Acid on Technological Ripening and Anthocyanin Profile of ‘Syrah’ Must and Grapes Grown in a Warm Climate - Sandoval-Silva, S.S.; Aispuro-Hernández, E.; Corrales-Maldonado, C.; Vargas-Arispuro, I.; Martínez-Téllez, M.A. (South African Journal of Enology and Viticulture, 2021)
The progressive increase of environmental temperature as a consequence of climate change is a challenge for the wine industry. Elevated temperatures during grape ripening affect the development of grape skin color by inhibiting the synthesis of pigments and promoting their degradation, which causes an imbalance in the chromatic quality of must and red wine. The application of pectic oligosaccharides (POs) and abscisic acid (ABA) triggers the phenylpropanoid pathway and increases the color index in grapes. Since the atharvest pigments and phenolic compounds are determinant for wine quality, this work addressed the preharvest application of POs and ABA as an in-field strategy for improving the quality of Syrah must and grapes grown in a warm climate. The color development, physicochemical parameters, phenolic content, and pigments in berries and must were evaluated. Results showed POs and ABA improved berry color development and anthocyanin content during ripening. Musts from POs-treated berries exhibited the highest phenols concentration and the most intense color, related to higher chroma values and anthocyanin content, particularly delphinidin, petunidin, and malvidin 3-glucosides, while ABA improved must tonality by reducing the hue angle. In summary, POs and ABA application at veráison, differentially modulated the technological ripening of Syrah grapes and can be an alternative to conventional agrochemicals to preserve the quality of musts elaborated from grapes grown in warm climates, by increasing the content of phenolic compounds and enhancing berry skin color development through the differential accumulation of anthocyanins.